THE PURPOSE AND AMBIT OF THE OFFENCE OF CONCEALMENT OF BIRTH S v Molefe 2012 (2) SACR 574 (GNP) - Shannon Hoctor; Marita Carnelley (Obiter, 2021)
The statutory offence of concealment of birth inevitably attracts controversy. It has been argued in the 2008 Canadian case of R v Levkovic (2008 CarswellOnt 5744, 235 CCC (3d) 417, 178 CRR (2d) 285, 79 WCD (2d) 493, heard in the Ontario Superior Court of Justice) that it is clear from the history of this offence that its purpose was to stigmatize socially and punish criminally women who bore illegitimate or “bastard” children – “an objective entirely offensive in modern society to liberty and security of the person”. Moreover, in the Memorandum on the Objects of the Judicial Matters Amendment Bill 2008 (B48-2008), the precursor of the South African statute which amended this offence, the criticism of the Women’s Legal Centre recorded that the provisions of section 113 of the General Law Amendment Act 46 of 1935 (which sets out the offence) are “overly broad, lacking in definition, archaic and their constitutional validity is questionable, often impinging on the right to dignity of women charged under it”. The purpose of this note is to examine these criticisms, assessing both the substantive aspects and constitutional aspects of the offence, in the course of an appraisal of the recent case of S v Molefe (2012 (2) SACR 574 (GNP)). The case of Levkovic will provide a useful comparative reference point for the inquiry into the constitutionality of the offence. First, however, it is necessary to place the offence in its historical context.